The Rb7Bi3−3xSb3xCl16 Family: A Fully Inorganic Solid Solution with Room‐Temperature Luminescent Members. Issue 34 (2nd July 2020) - Benin, Bogdan M.; McCall, Kyle M.; Wörle, Michael; Morad, Viktoriia; Aebli, Marcel; Yakunin, Sergii; Shynkarenko, Yevhen; Kovalenko, Maksym V.
Abstract: Low‐dimensional ns 2 ‐metal halide compounds have received immense attention for applications in solid‐state lighting, optical thermometry and thermography, and scintillation. However, these are based primarily on the combination of organic cations with toxic Pb 2+ or unstable Sn 2+, and a stable inorganic luminescent material has yet to be found. Here, the zero‐dimensional Rb7 Sb3 Cl16 phase, comprised of isolated [SbCl6 ] 3− octahedra and edge‐sharing [Sb2 Cl10 ] 4− dimers, shows room‐temperature photoluminescence (RT PL) centered at 560 nm with a quantum yield of 3.8±0.2 % at 296 K (99.4 % at 77 K). The temperature‐dependent PL lifetime rivals that of previous low‐dimensional materials with a specific temperature sensitivity above 0.06 K −1 at RT, making it an excellent thermometric material. Utilizing both DFT and chemical substitution with Bi 3+ in the Rb7 Bi3−3 x Sb3 x Cl16 ( x ≤1) family, we present the edge‐shared [Sb2 Cl10 ] 4− dimer as a design principle for Sb‐based luminescent materials. Abstract : The Rb7 Sb3 Cl16 phase, comprised of isolated octahedra and edge‐shared dimers, demonstrates photoluminescence centered at 560 nm with a quantum yield of 3.8 % at 296 K (99.4 % at 77 K) and a specific temperature sensitivity above 0.06 K −1 at 300 K. Utilizing DFT and chemical substitution with Bi 3+ in the Rb7 Bi3−3 x Sb3 x Cl16 ( x ≤1) family, the [Sb2 Cl10 ] 4− dimer is presented as a design principle for Sb‐based luminescent materials.